2015
DOI: 10.4103/1658-354x.146304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low dose tranexamic acid on intra-operative blood loss in neurosurgical patients

Abstract: Background:Blood loss is often a major complication in neurosurgery that requires transfusion of multiple units of blood. The purpose of this study was to assess the effect of tranexamic acid (TXA) on intraoperative blood loss and the need for blood transfusion in patients undergoing craniotomy for tumor excision.Materials and Methods:A total of 100 patients aged 18-60 years, with American Society of Anesthesiologists physical Status 1 and 2 scheduled to undergo elective craniotomy for tumor excision were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…After careful consideration from each authors, we decided to include three studies. [ 19 , 37 , 39 ] All of them were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After careful consideration from each authors, we decided to include three studies. [ 19 , 37 , 39 ] All of them were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…It was not clearly stated who prepared the TXA. [ 37 ] Vel et al . used a computer-generated randomization chart to allocate the patient.…”
Section: Resultsmentioning
confidence: 99%
“…Many RCTs have shown that TXA treatment could considerably reduce the risk of rebleeding [11-13, 15, 16], the curative effect is closely related to its pharmacological action [19,20]. TXA can inhibit brinolysis by replacing plasminogen from brin and also inhibits enzymatic degradation by plasmin [21,22]. Nevertheless, in the recent publication of the ULTRA, rebleeding after randomization and before aneurysm treatment occurred in the tranexamic acid and control group did not reach the prede ned threshold for statistical signi cance, perhaps because half of the rebleeding occurred within 3 hours, in this trial, the median interval time from symptomatic onset to treatment was 3 hours, a considerable proportion of rebleeds had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The studies including patients with liver, prostate and gynecological cancer found a reduction in blood transfusion requirements during and after surgery in the TXA arms [ 36 , 37 , 38 , 39 , 40 , 41 ]. In contrast, antifibrinolytics did not influence bleeding outcomes in major orthopedic cancer surgery or in oncologic spinal canal, head and neck and neurosurgeries [ 42 , 43 , 44 , 45 ].…”
Section: Managing Thrombocytopenia In Cancermentioning
confidence: 99%